A likelihood framework analysis of an island radiation: phylogeography of the Lesser Antillean gecko Sphaerodactylus vincenti, in comparison with the anole Anolis roquet. (18th October 2012) - Surget‐Groba, Yann; Thorpe, Roger S.
Abstract: Aim: The West Indies have hosted several spectacular radiations, including that of the litter geckos of the genus Sphaerodactylus . We analyse the phylogeography of the Sphaerodactylus vincenti complex and explore the possibility that there may be cryptic species to be revealed. Postulated colonization routes in this complex are estimated and compared with those of co‐distributed lizards (the Anolis roquet complex). Location: Lesser Antilles. Methods: Phylogenetic relationships (gene trees) were estimated using maximum parsimony and Bayesian analysis of the cytochrome b sequence [mitochondrial DNA (mtDNA)] obtained from 53 individuals sampled in Dominica, Martinique, St Vincent, Bequia and Mustique. The Bayesian relaxed‐clock method was used to estimate the time to the most recent common ancestor and a likelihood framework analysis was employed to probabilistically estimate the geographic origin of the main clades of the S. vincenti complex. These methods were repeated on the co‐distributed species complex of A. roquet, and their timing and colonization routes were compared. Results: Phylogenetic analysis of mtDNA of the S. vincenti complex in the Lesser Antilles reveals a deep split between the northern (north Martinique and Dominica) and southern (south Martinique, St Vincent, Grenadines and possibly St Lucia) clades with about 22% mean divergence. Together with geological information, these results suggest that Martinique is occupied by populations that began evolving in allopatry 12.5 million years ago, and which came into secondary contact once precursor islands coalesced to produce present‐day Martinique. Main conclusions: We regard the two main forms of Sphaerodactylus as separate species based on their substantial mtDNA divergence and largely diagnostic scapula ocelli (present in the north, but largely absent in the south). Although there are similarities in the precursor islands occupied by the Anolis and Sphaerodactylus species, their colonization sequence is different, probably due to the stochastic nature of the long‐distance dispersal involved in island colonization.